2019
DOI: 10.1109/access.2019.2957206
|View full text |Cite
|
Sign up to set email alerts
|

Applying the UTAUT Model to Explain the Students’ Acceptance of Mobile Learning System in Higher Education

Abstract: Mobile learning applications have been growing in demand and popularity and have become a common phenomenon in modern educational systems, especially with the implementation of mobile learning projects. This study applies the Unified Theory of Acceptance and Use Technology (UTAUT) model to examine the effects of different factors that were identified from the literature on students' acceptance of mobile learning applications in higher education. The data was collected from a 697 university students responded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
165
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 214 publications
(254 citation statements)
references
References 45 publications
(100 reference statements)
19
165
4
3
Order By: Relevance
“…In contrast, the findings of this study were found to be in-line with the results of other studies that reported increasing levels of academic achievement, collaboration, and knowledge sharing in online courses compared to face-to-face and traditional courses [22,57,59]. In spite of the beneficial impact of (SNAs) via collaboration and engagement as sustainability in higher education, it is still reported that this technology is still underused in classrooms and is rarely involved in traditional classes [3]. As mentioned by [62], there is an increasing tendency to use social internet networks and various multimedia contents for the purpose of exchanging information.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, the findings of this study were found to be in-line with the results of other studies that reported increasing levels of academic achievement, collaboration, and knowledge sharing in online courses compared to face-to-face and traditional courses [22,57,59]. In spite of the beneficial impact of (SNAs) via collaboration and engagement as sustainability in higher education, it is still reported that this technology is still underused in classrooms and is rarely involved in traditional classes [3]. As mentioned by [62], there is an increasing tendency to use social internet networks and various multimedia contents for the purpose of exchanging information.…”
Section: Discussionsupporting
confidence: 88%
“…The study observed (SNAs) to be an important technology in enhancing the voice of students and improvement in the learning process. In another study by [3], students were found to be more susceptible in using Facebook and other (SNAs) platforms to strengthen the learning processes in comparison to others who are focused towards using conventional learning methods.…”
Section: B (Snas) In Educationmentioning
confidence: 96%
See 2 more Smart Citations
“…Hsu, Hwang, Chuang, and Chang [39] showed that students using open networks perceived their usefulness and had high intentions to use the online resources. PU was observed as the largest influencer to adopting mobile technology [40][41][42]. Furthermore, in educational contexts, usefulness was observed by [43] as one of the most relevant factors for teachers to adopt SMAs in their lessons.…”
Section: Pumentioning
confidence: 92%